FEATURES of NON-DESTRUCTIVE damage CONTROL OF aircraft parts made of composite MATERIALS at the enterprises of aviation industry - A. V. Kopylov; B. V. Zubkov (Научный вестник МГТУ ГА, 2016)
The article describes the urgent problems which can arise at enterprises of aviation industries by the operating air during non-destructive damage control of products made of composite materials used in aircraft. The methods of control are very specific due to have a number of peculiarities in detecting damages in view of the complicated composite materials structure.